PjBL Model with the Context of Making Liquid Organic Fertilizer (LOF) from Bamboo Shoots to Build Students' Critical Thinking Skills - Omay Sumarna; Ruci Aditya Rushiana (Postgraduate, University of Mataram, 2023)
This study aims to obtain information about students' critical thinking skills (CTS) through the application of the project based learning (PjBL) model on reaction rate material in the context of making liquid organic fertilizer (LOF) from bamboo shoots. The method used is an experimental method with a one-group pretest-posttest design. This study uses one class with a total of 27 students. The instruments used were observation sheets on the implementation of learning and tests of critical thinking skills which consisted of 15 multiple-choice questions. Test result data were processed using the N-gain test and paired sample t-test. The results showed that the application of the PjBL model in the context of making LOF from bamboo shoots obtained a learning implementation percentage of 85.4 and was included in the very good category. In addition, the CTS of students as a whole experienced an increase of 0.69 in the moderate category. The results of the paired sample t-test show that the significance value obtained is 0.000 <0.05 so it can be concluded that there is an increase in the CTS of students through learning.